Synthesis and Characterization of Carrageenan-Chitosan Milkfish Scales-Based Hydrogel for Slow-Release Fertilizer - Asri Azizah; Diana Triyanti; Putri Sahira; Anisa Putri; Retno Sulistyo Dhamar Lestari; Jayanudin Jayanudin (ALCHEMY Jurnal Penelitian Kimia, 2026)
This study aims to develop a superabsorbent hydrogel as a slow-release fertilizer based on a combination of carrageenan-glucomannan and carrageenan-chitosan derived from milkfish (Chanos chanos) scale waste. The hydrogel was synthesized by chemical crosslinking with glutaraldehyde concentrations of 2%, 4%, 6%, and 8%. Hydrogel characterization included swelling ratio tests, gel fraction analysis, Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), urea absorption (Xo), and urea release kinetics in both aqueous and soil media. The results indicate that a 8% glutaraldehyde concentration yielded optimal performance in both hydrogel systems, achieving the highest gel fractions (>90%) and maximum urea absorption capacities of 8.05 g/g for carrageenan-glucomannan and 13.31 g/g for carrageenan-chitosan. The carrageenan-glucomannan hydrogel exhibited a higher swelling ratio of 630% at 2% glutaraldehyde concentration and slower urea release in soil, ranging from 0.192% to 4.113% over 7 days. In contrast, the carrageenan-chitosan hydrogel demonstrated stronger chemical affinity for urea but released it more rapidly, ranging from 1.037% to 7.092% over the same period. SEM and FTIR analyses confirmed the formation of a three-dimensional network structure and chemical interactions among the components.